The needs and satisfaction among family members during COVID-19 pandemic in intensive care unit (ICU) Hospital Universiti Sains Malaysia - Norazman, Fatin Umairah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
ICU is a structured system for providing care to critically ill patients that includes intensive and specialized medical and nursing care, increased monitoring capacity and multiple modalities of physiologic organ support to help patients survive during a period of life-threatening organ system insufficiency. The needs and the satisfaction level on the ICU patient family’s studies have gained attention among the medical researcher since the questionnaire is widely known and reliable to use. A cross-sectional study has been conducted to identify the needs and level of satisfaction among family members during Covid-19 pandemic in ICU HUSM. This study also examined the correlation between the needs and satisfaction among family members during Covid-19 pandemic in ICU HUSM. Pearson correlation was used to examined the correlation between the needs and satisfaction among family members during Covid-19 pandemic in ICU HUSM. A total of 85 respondents were involved with this study by using convenience sampling. Data were collected from March 2022 to May 2022 by using google form and analyzed using SPSS version 26.0 for a window. Most of the respondents are female respondents (68.2%). The results revealed that the rank order of the needs were Assurance, followed by Support, Information, Comfort and Proximity. It also revealed the level of satisfaction; Consideration of Your Needs, Concern and Caring, followed by Skill, Competence and Atmosphere in ICU. The highest need was Assurance (Mean = 45.61, SD = 2.55) the least need was Proximity (Mean = 18.28, SD = 3.50) while the highest satisfaction is Consideration of Your Needs (Mean = 22.54, SD = 2.30) among the family members.